2007
DOI: 10.1063/1.2713856
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the drain current bistability in polymer ferroelectric field-effect transistors

Abstract: Origin of the drain current bistability in polymer ferroelectric field-effect transistors Naber, R. C. G.; Massolt, J.; Spijkman, M.; Asadi, K.; Blom, P. W. M.; de Leeuw, D. M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 17 publications
(13 reference statements)
4
79
1
Order By: Relevance
“…It is known from literature that p-type semiconductors are not good at providing compensating electrons and vice versa. [40][41][42][43] As the deposition of a layer of H-PSS or Nafi on occurs from an acidic solution, it was checked whether spin coating instead with a 1 M H 2 SO 4 solution on Au gave similar results. This step actually results in washing the electrode with an acidic solution.…”
Section: Work Function Increase By H-pss and Nafi Onmentioning
confidence: 96%
“…It is known from literature that p-type semiconductors are not good at providing compensating electrons and vice versa. [40][41][42][43] As the deposition of a layer of H-PSS or Nafi on occurs from an acidic solution, it was checked whether spin coating instead with a 1 M H 2 SO 4 solution on Au gave similar results. This step actually results in washing the electrode with an acidic solution.…”
Section: Work Function Increase By H-pss and Nafi Onmentioning
confidence: 96%
“…From this consideration, many researchers believed that such large depolarization field did the main contribution to the much faster degradation of this depletion state. 10,11 However, further study indicates that if depletion voltage is high enough, semiconducting layer can be switched to inversion and minority carriers can accumulate at ferroelectric/semiconductor interface to compensate polarization charges. Thus ferroelectric polarization is expected to be stable.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers argued that the hysteresis was due to bistable positive and negative polarization states of the P(VDF-TrFE) film, [5][6][7] while there were still some consideration that the cause of hysteresis was due to one polarization state and one depolarization state. 10 Furthermore, the whole C-V curves shift toward positive voltage direction, which should be due to the existence of space charges in Al 2 O 3 layer and/or ferroelectric films injected during the electrical application. These space charges produce an internal electric field resulting in the shift of the transition voltage from the accumulation to the inversion states and vice versa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For organic semiconductors in contact with the ferroelectric random copolymer poly͑vinylidene fluoride-cotrifluoroethylene͒ ͓P͑VDF-TrFE͔͒ Naber et al 10 have shown that polarization in metal-ferroelectric insulatorsemiconductor diodes only occurs when majority carriers, in this case injected from a back contact, provide compensation. However, when the majority carriers are depleted, the ferroelectric depolarizes.…”
mentioning
confidence: 99%